A qualitative study of overweight and obese Australians' views of food addiction. (1st August 2017) - Cullen, A.J.; Barnett, A.; Komesaroff, P.A.; Brown, W.; O'Brien, K.S.; Hall, W.; Carter, A.
Abstract: The concept of food addiction is increasingly used in the academic literature and popular media to explain some forms of overweight and obesity. However, there is limited evidence on how this term is understood by and impacts overweight and obese individuals. This qualitative study investigated the views of overweight and obese individuals on food addiction, and its likely impact upon stigma, treatment-seeking, and support for public policies to reduce overeating. Semi-structured interviews were conducted with 23 overweight and obese individuals ( M age  = 38, M BMI  = 33, 74% female) and analysed thematically. The concept of food addiction was consistent with many participants' personal experiences, and was accompanied by high perceptions of control and personal responsibility. Some participants believed "sugar" or "fat" addiction to be more accurate. Others were reluctant to be described as an "addict" owing to perceived negative connotations and the belief that it would increase self-stigma. Food addiction was seen as a motivator for seeking psychological services, but not pharmaceutical or surgical treatments. In light of food addiction being perceived as plausible and relevant, participants supported targeted public health policies (e.g., taxes, regulations for junk food container sizes) but did not believe these would affect their own purchasing or consumption behaviours. Education for interpreting food labels and reducing the costs of healthy foods were endorsed, leading to positive changes in food-related behaviours. This research suggests discretionary use of the food addiction label in a supportive and educational manner to minimise stigma while encouraging treatment-seeking.